The Role of Probiotics in Modulating Myocardial Infarction and Depression-like Symptoms: A Study on Sex-Specific Responses - Marc-André Gagné; Geneviève Frégeau; Roger Godbout; Guy Rousseau (Biomedicines)
Background/Objectives: This study explores the effects of two probiotics, Lactobacillus helveticus R0052 and Bifidobacterium longum R0175, on myocardial infarction (MI) and associated depression-like behaviours, with a focus on sex differences. Methods: MI was induced in adult male and female rats by occluding the left anterior coronary artery for 30 min, followed by 24 h of reperfusion. Probiotics were administered via drinking water for at least two weeks before ischemia. Infarct size, plasma C-reactive protein (CRP), estradiol levels, and intestinal permeability were then measured. Two weeks after, MI subgroups of rats were tested for depression-like behaviours. Results: We found a significant interaction between sex and probiotics in relation to infarct size. Probiotics significantly reduced the infarct size compared to the vehicle group in female rats but not in males. Probiotics increased the plasma estradiol levels and reduced the CRP concentrations in females, suggesting anti-inflammatory and cardioprotective properties. Probiotics significantly increased intestinal resistance following MI in males only, suggesting sex-specific physiological responses to treatment. Probiotics enhanced social interaction in males with MI but not in females. Similarly, in the forced swim test, probiotics reduced immobility in males with MI but increased it in females, further underscoring the sex-dependent effects of probiotics. Conclusions: This study reports cardioprotective effects of probiotics upon MI in female rats, while benefits in male rats were rather at the behavioural level. These results highlight distinct physiological and behavioural responses between sexes, emphasizing the need to account for sex differences in future tests of probiotics as a prophylactic treatment for MI.